Drilling fluid for Dome F Project in Antarctica - Fujita, Shuji; Yamada, Tomomi; Naruse, Renji; Mae, Shinji; Azuma, Nobuhiko; Fujii, Yoshiyuki (1994)
P(論文) At Dome F, one of the summits of the East Antarctic Ice Sheet, a very deep ice-coring operation is to be carried out by the Japanese Antarctic Research Expedition from 1995. Since it will take two years to complete the coring up to about 3000m depth, the borehole should be filled with proper drilling fluid to prevent borehole closure during the operation. This paper is a report on our investigations for searching for the proper drilling fluid which can be used in the very cold environment at Dome F. Although the investigations are still in progress, three kinds of fluid were chosen as drilling fluid candidates. They are : 1) n-butyl acetate, 2) "IP-solvent" with densifier and 3) Silicone Oil. Their properties were investigated and compared in terms of density and viscosity, which are essential requirements for a drilling fluid. As a result, it was shown that n-butyl acetate and IP-solvent with densifier can be used as the drilling fluid. However, the use of n-butyl acetate is impossible without sufficient ventilation at the coring site or other action to dispose of its vapor. When the use of IP-solvent with densifier is considered, the choice of proper densifier is also a problem. departmental bulletin paper